IDENTIFIKASI PERSEBARAN AIR LINDI MENGGUNAKAN METODE VERY LOW FREQUENCY ELECTROMACNETIC (VLF-EM) DI TPA PUUWATU, KOTA KENDARI - David Satria; Erzam S. Hasan; Al Rubaiyn; La Ode Ngkoimani (Jurnal Rekayasa Geofisika Indonesia, 2021)
Leachate which is a liquid released from waste due to biological degradation processes. If the leachate flow is allowed to flow to the surface of the soil, it will have negative effects on the surrounding environment. One of the geophysical methods that can be used to detect leachate distribution patterns is the VLF-EM (Very Low Frequency-Electromagnetic) method. The VLF-EM (Very Low Frequency-Electromagnetic) method is a geophysical method that utilizes electromagnetic principles using a low frequency radio wave source of 10-30 kHz. The research location is in TPA Puawatu, Kendari City. The analysis was carried out by looking at the 2D cross section of the flow density gained from the data processing. Qualitative interpretation can be carried out by the method developed by Karous-Hjelt with the producing of a 2-dimensional cross section with current density parameters. The high current density value can be identified as the most conductive anomaly. The direction of leachate distribution in the Puuwatu TPA tends to flow from the north of the TPA to the south of the TPA, which indicates that many swamps in the South of the TPA have been contaminated with leachate.